Comportamento dinâmico de pórticos metálicos ao acoplar absorvedores dinâmicos de vibrações do tipo viga com massa na ponta - Zenatti, Carlos Natã (2025)
This work investigates the dynamic behavior of metallic structural systems supported by Tuned Mass Damper (TMDs) of the beam type with mass at the tip, with a view to controlling vibrations and improving structural performance. The research is divided into two cases: in the first (Case 1), a numerical analysis using the Finite Element Method (FEM) was carried out to model the Case 2 frame in a simplified way and to evaluate the efficiency of eight TMDs designed using the maximum deflection and mass ratio methods. In addition, the study aims to propose a simplified analytical model with 3 Degrees Of Freedom (DOF) to compare with numerical results. Thus, in the numerical model, the results showed a significant reduction in the acceleration amplitude of the first natural frequency, as well as highlighting the influence of TMDs with greater masses on structural dynamics. As for the analytical model, the results indicate good convergence with the numerical model, with the disagreements being correlated to the modal superposition method and the low number of DOF. In the second case (Case 2), an experimental modal analysis was carried out on a frame, validating the numerical model (more complex than Case 1) with an error of only 0.01% in the target frequency. Four TMDs were designed and tested numerically, with results indicating high efficiency even for TMDs with smaller masses. One of the TMDs was manufactured and applied experimentally, resulting in a reduction in the acceleration amplitude of the first natural frequency, as well as attenuating the amplitudes in all modes of the target direction. The results confirm the effectiveness of using TMDs to attenuate vibrations in metallic structures, contributing to advances in the dynamic control of structural systems and the safety of practical applications.